Pomen Evropske socialne listine za varstvo delavskih pravic - Kresal, Barbara (Delavci in delodajalci, 2020)
The European Social Charter, signed in 1961 in Turin, together with its additional protocols and the Revised version from 1996 is the Council of Europe`s human rights instrument which guaranties economic and social human rights, among them also individual and collective labour rights. The contribution presents its development over time, its general structure and the supervisory machinery, such as the reporting system and the collective complaints procedure, and focuses on the relevant Charter provisions on labour rights. Recent case-law of the European Committee of Social Rights (ECSR) in the area of labour rights is presented. Special attention is given to the ECSR Conclusions 2018. Decisions on the UWE complaints (the right to equal pay) and in the case ICTU v. Ireland (the right to collective bargaining for the self-employed workers) are shortly presented as well.
Keywords: collective bargaining for the self-employed; collective complaint; delavske pravice; enako plačilo; equal pay; European Committee of Social Rights; European Social Charter; Evropska socialna listina; Evropski odbor za socialne pravice; fundamental social rights; kolektivna pritožba; kolektivno pogajanje za samozaposlene; labour rights; reporting system; sistem poročanja; social security; socialna varnost; socialno pravo; temeljne socialne pravice